2020
DOI: 10.22541/au.159603674.42072283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Routine use of del Nido Cardioplegia compared to blood cardioplegia in all types of adult cardiac surgery procedures

Abstract: Background and aim of the study: Several studies reported safety and potential benefits of single dose Del Nido cardioplegia (DNC) in selected Adult Cardiac Surgery (ACS) procedures. However, studies are scarce on routine use of DNC in more complex procedures and patients with high risk profile. We sought to compare DNC with cold blood cardioplegia (BC) in all types of ACS including complex procedures. Methods: Data for 305 consecutive unselected patients who underwent ACS procedures (July/2017 to Nov/2019) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Twelve studies involving 5065 patients reported on the use of IABP. 22,2628,30,31,33,36,42,49,55,57 There was no statistically difference between the groups in terms of the incidence of the use of IABP (RR: 1.10, 95% CI: 0.87 to 1.39, p = 0.44, see Supplemental Figure 3A). As many as 17 studies with 3134 patients in total showed the result of postoperative inotropic agent use, 7,21,23,26,2830,36,4143,49,5458 and it was also comparable between the two groups (RR: 1.02, 95% CI: 0.94 to 1.10, p = 0.67, see Supplemental Figure 3B).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Twelve studies involving 5065 patients reported on the use of IABP. 22,2628,30,31,33,36,42,49,55,57 There was no statistically difference between the groups in terms of the incidence of the use of IABP (RR: 1.10, 95% CI: 0.87 to 1.39, p = 0.44, see Supplemental Figure 3A). As many as 17 studies with 3134 patients in total showed the result of postoperative inotropic agent use, 7,21,23,26,2830,36,4143,49,5458 and it was also comparable between the two groups (RR: 1.02, 95% CI: 0.94 to 1.10, p = 0.67, see Supplemental Figure 3B).…”
Section: Resultsmentioning
confidence: 94%
“…Mechanical ventilation time was reported in 12 studies involving 1849 patients. 7,21,23,28,39,40,42,44,51,54,56,57 The time was found to be significantly less in the DNC group (MD: −0.62, 95% CI: −1.19 to -0.05, p = 0.03, Figure 4(a)). Twelve studies involving 5065 patients reported on the use of IABP.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations